Pengaruh Proporsi Tepung Ubi Jalar Ungu (Ipomoea Batatas L.) Dan Tepung Kacang Merah (Phaseolus Vulgaris L.)Pratanak Pada Pembuatan Food Bar Terhadap Daya Patah Dan Daya Terima - Wulandari, Anggraini; , Retty Ikawati, S.TP., M.Sc; , Luluk Ria Rakhma, S.Gz., M.Gizi (2017)
Purple sweet potato is local food that can be processed into food bar. Parboiled red bean flour can be used to increase the fiber content. Purple sweet potato flour with red beans parboiled flour may affect the chemical quality, physical quality and sensory quality of the food bar. The purpose of the research was to determine the effect of purple sweet potato and parboiled red beans proportion to the brittleness and acceptance of the food bar. This research was conducted by proportion of purple sweet potato and parboiled red beans with different treatment variation with 90 : 10; 80 : 20; dan 70 : 30. The results showed that sweet potato and parboiled red beans different proportions did not affect the brittleness of food bar. The acceptence of purple sweet potato and parboiled red beans different sample affect on texture and overall, but did not affect to the aroma, color, and taste. The best acceptance of foodbar with proportion of 90 : 10, followed by 80 : 10.